Corruption Practices Among Young Elective Public Officials (Sanggunian Kabataan) In Iligan City, Southern Philippines - Sulpecia L. Ponce; Domshell John B. Cahiles; Mohammad Naif S. Pimping; Jonathan A. Jangao; Amabelle A. Embornas; Myrma Jean A. Mendoza (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2013)
This study attempts to explore the involvement in graft and corruption among elective barangay youth officials in a city in Southern Philippines. Using a qualitative research design employing a case study method, 10 informants were included in this study and were selected using snowball sampling technique. The findings indicated that the informants were aware of the forms of graft and corrupt practices stipulated in the Anti-Graft and Corrupt Practices Act in the Philippines (RA 3019) and other legal documents. However, despite this, most of them admitted to have been involved in any of the following irregular acts while in public service: malversation of public funds, evasion of public bidding in the purchase of supplies and equipments, forgery, bribery, making ghost projects and payrolls, abuse of powers, among others. It was known also that corruption was caused mainly by bureaucratic dysfunctions especially in the delay of budget releases and political socialization with older and corrupt barangay officials who passed on the techniques of corruption to the young leader informants. The policy implications of the study demands further strengthening of governmental structures and processes that would ensure observance of good governance among public officials both at the barangay (local) and national levels.